Pengaruh partisipasi masyarakat dalam pencegahan demam berdarah dengue (DBD) terhadap peningkatan kejadian DBD di Wilayah kerja Puskesmas Tegallalang I - Norhara Noorsham Kamal; Made Dharmadi (Intisari Sains Medis, 2017)
This study was conducted to determine the image's participation in the prevention of DHF carried by people in Puskesmas Tegallalang I and prove that the participation of poor people prevention has experienced a higher risk for suffering from DHF. Methods: This was an analytic observational study with case control design. In this study, the researchers distinguish the population into two, namely the population of cases and population control / comparator (not the case). Samples in the case group number of 28 cases were determined by quota sampling technique selected and adapted to the proportion of each banjar in that village. The instrument used was a questionnaire. Results: The results showed as many as 60.7% had poor participation (value score of questionnaire 0-18). While in the control group, only 37.5% had poor participation. From 84 research samples, amounting to 45.2% or 38 people have poor participation on the prevention of DHF. Results showed the value of the odds ratio (OR) of 2.57 with a 95% confidence interval (1.01 to 6.53). Hypothesis test Chi Square shows the results of p = 0.04. It showed statistically with the participation of poor groups will have the possibility of 2.57 times to suffer from DHF than either group participation. Conclusion: Overview of participation in dengue prevention is done by people in Puskesmas Tegallalang I mostly included the participation of both groups. There are significant community participation in prevention of DHF to the increased incidence of DHF in Puskesmas Tegallalang I.